Policy Formulation of Criminal Law against Narcotics Traffickers Based On Justice Value - Ade Christian Manapa (Jurnal Daulat Hukum, 2019)
Act No. 35 of 2009 on Narcotics there are multiple interpretations and ambiguities article formulation, namely Article 112 of Law on Narcotics. Article resulted in the perpetrators of Narcotics (trafficker) will shelter as if he was a victim of crime or narcotics abusers.The problems are: 1) Are Policy Formulation of Criminal Law Against Narcotics Traffickers based on Act No. 35 of 2009 has fulfilled a Justice Value? 2) How does the Policy Formulation of Criminal Law Against Narcotics Traffickers in Criminal Justice in Indonesia? and 3) how the Policy Formulation of Upcoming Criminal Law Against The Perpetrators And Abusers Based on Justice Value?The method used is normative, the specification of the research is descriptive analytical data using secondary data sources, data collection methods using literature study, data presentation in the narrative, qualitative data analysis. The research problem in accordance with the above described problems he infused with three theories: 1) The theory of law enforcement, 2) Theory of legal certainty and 3) Theory of justice.Result: 1) Policy Formulation of Criminal Law Against Narcotics Traffickers Based On Act No. 35 of 2009 still indicates ambiguity and multiple interpretations. Between the formulation of article 112 and article 127 so that it can ensnare abusers of narcotics in Article 127.2) Policies application of criminal law against traffickers Narcotics in Criminal Justice in Indonesia is still problematic, where the dealer the crime of Narcotics can shelter as abusers of narcotics to avoid criminal sanctions are more severe. 3) Policy criminal law traffickers and abusers of narcotics in the future is the need to change the formulation of Article 112 Law on Narcotics, ie there must be firmness that met the elements "have", "save", "master" or "buy" is a chapter devoted to trafficker, importers, producer, and another narcotics crime qualification and not pointed to narcotic abuse itself.Keywords: Policy Formulation of Criminal Law; Narcotics Traffickers; Justice Value.